Cognitive behavioral therapies for informal caregivers of patients with cancer and cancer survivors: a systematic review and meta‐analysis. Issue 4 (5th May 2016) - O'Toole, Mia S.; Zachariae, Robert; Renna, Megan E.; Mennin, Douglas S.; Applebaum, Allison
Abstract: Objective: Informal caregivers (ICs) of patients with cancer and cancer survivors report a number of psychological and physical complaints because of the burden associated with providing care. Given the documented effect of Cognitive Behavioral Therapy (CBT) on ICs' common psychological complaints, such as anxiety and depression, the objective was to conduct a meta‐analysis on the effect of CBTs for adult ICs. Methods: A literature search was conducted in order to identify all intervention studies on adult ICs that employed at least one therapeutic component defined as a CBT component. Results: Literature searches revealed 36 unique records with sufficient data. These studies were subjected to meta‐analyses using random effects models. A small, statistically significant effect of CBTs (Hedge's g  = 0.08, p  = 0.014) was revealed, which disappeared when randomized controlled trials were evaluated alone ( g  = 0.04, p  = 0.200). A number of variables were explored as moderators. Only the percentage of female participants was positively associated with the effect size. Conclusions: Based on the negligible effect of CBTs across outcomes, future studies should consider moving beyond traditional CBT methods as these do not appear efficacious. It is suggested that future interventions orient towards advances in the basic affective sciences and derived therapies in order to better understand and treat the emotional struggles experienced by ICs. © 2016 The Authors. Psycho‐Oncology published by John Wiley & Sons Ltd.